Method of non-destructive control of thickness and internal defectivity of the walls of metal pipe - S. A. Zolotarev; P. S. Savenia; K. A. Zhukov; M. A. Sednina (Системный анализ и прикладная информатика)
The possibility of an accurate estimation of the pipe wall thickness measured directly from the reconstructed image of the pipe, reconstructed from only a few X-ray projections made in a limited viewing angle, is discussed. Since the effects of radiation scattering and X-ray beam hardening distort up to 50 % of the primary radiation, ignoring these effects leads to blurred images, strong artifacts, and inaccurate sizing. A computerized technique has been developed that takes into account the contribution of scattered radiation and the hardening of the X-ray beam. Iterative Bayesian reconstruction techniques are then used to reconstruct the pipe image using the volumetric and surface-oriented representation of the pipe. Using these methods, the error in estimating the pipe wall thickness can be increased to 300 microns.